Do risk factors differentiate DSM-5 and drive for thinness severity groups for anorexia nervosa? - An Binh Dang; Litza Kiropoulos; Marija Anderluh; David Collier; Fernando Fernandez-Aranda; Andreas Karwautz; Janet Treasure; Gudrun Wagner; Isabel Krug (Journal of Eating Disorders, 2024)
Abstract Background The current study examined whether risk factors for anorexia nervosa (AN) were related to different levels of severity based on (a) the DSM-5/body mass index (BMI) and (b) drive for thinness (DT) severity ratings. Methods The sample comprised 153 pairs of individuals with a lifetime diagnosis AN per DSM-IV criteria and their non-ED sisters (N = 306, mean age = 26.53; mean current BMI = 20.42 kg/m2). The Oxford risk factor interview was used to establish AN-related risk factors. Individuals were categorised into the DSM-5 severity groups based on their lowest BMI, while the DT subscale from the eating disorder inventory-2 was used to classify individuals with AN into low and high DT groups. Results Multinominal regression models showed similar risk factors (e.g., perfectionism, having a history of being teased about weight and shape) contributed to the development of AN using the DSM-5 and DT severity ratings. Follow-up analyses across the severity groups for both indices revealed that only childhood perfectionism was found to be more common in the extreme severe DSM-5 BMI severity group compared to the severe DSM-5 group. Conclusion Overall, this study found little evidence for AN risk factors being related to the DSM-5 and DT severity ratings. However, given the novelty of this study, replication of the current results is warranted.